THE EXPRESSION TOPONYMS IN THE FUNCTION OF NUCLEAR COMPONENTS IN ENGLISH AND UZBEK LANGUAGES - Jumatov Rashid Yangibaevich (EPRA International Journal of Research and Development (IJRD), 2022)
This article is dedicated to the comparative study of toponyms in the English and Uzbek languages, in which the place names functioning as nuclear components are analyzed based on modern linguistic methods. In particular, the syntactic relations of toponyms in the sentence are explained on the basis of junctional models, and their morphological features are revealed through component models. Also, their similarities and differences in these unrelated languages ​​have been identified. This article may be useful for linguistic researchers and those interested in toponymy and/or functional syntax.